Urban policy mobilities: recent debates and future research agendas - Silva, Diogo Gaspar (2024)
This paper introduces and discusses the interdisciplinary approach of urban policy mobilities. It begins by reviewing its intellectual antecedents, which the paper argues are rooted in architectural and planning histories, anthropology, cultural and social geography, and political science. Since its emergence in the early 2000s, the approach has expanded significantly. This paper provides a balanced overview of both persistent and still-nascent theoretical and empirical themes or issues structuring the approach. Taking stock of these features and drawing intellectual contributions from within and beyond the social sciences, the paper concludes by arguing for four possible future research pathways for urban policy mobilities Keywords: policy mobilities, policy transfer, urban policy; urban politics, urban policy making, public policy, urban geography.